TYK2 Promoter Variant and Diabetes Mellitus in the Japanese - Seiho Nagafuchi; Yumi Kamada-Hibio; Kanako Hirakawa; Nobutaka Tsutsu; Masae Minami; Akira Okada; Katsuya Kai; Miho Teshima; Arisa Moroishi; Yoshikazu Murakami; Yoshikazu Umeno; Yasushi Yokogawa; et al. (EBioMedicine, 2015)
Background: Recently, natural mutation of Tyrosine kinase 2 (Tyk2) gene has been shown to determine susceptibility to murine virus-induced diabetes. In addition, a previous human genome-wide study suggested the type 1 diabetes (T1D) susceptibility region to be 19p13, where the human TYK2 gene is located (19p13.2). Methods: Polymorphisms of TYK2 gene at the promoter region and exons were studied among 331 healthy controls, and 302 patients with T1D and 314 with type 2 diabetes (T2D) in the Japanese. Findings: A TYK2 promoter haplotype with multiple genetic polymorphisms, which are in complete linkage disequilibrium, named TYK2 promoter variant, presenting decreased promoter activity, is associated with an increased risk of not only T1D (odds ratio (OR), 2.4; 95% confidence interval (CI), 1.2 to 4.6; P = 0.01), but also T2D (OR, 2.1; 95% CI, 1.1 to 4.1; P = 0.03). The risk is high in patients with T1D associated with flu-like syndrome at diabetes onset and also those without anti-glutamic acid decarboxylase autoantibody. Interpretation: The TYK2 promoter variant is associated with an overall risk for diabetes, serving a good candidate as a virus-induced diabetes susceptibility gene in humans. Funding: Ministry of Education, Culture, Sports, Science and Technology and of Health, Labor and Welfare of Japan.